Improved Value of Individual Prenatal Care for the Interdisciplinary Team. (17th September 2018) - Damiano, Ella; Theiler, Regan
Abstract : Objective . Innovative models of prenatal care are needed to improve pregnancy outcomes and lower the cost of care. We sought to increase the value of traditional prenatal care by using a new model (PodCare) featuring a standardized visit schedule and coordination of care within small interdisciplinary teams in an academic setting. Methods . Prenatal providers and clinic staff were divided into four "Pods". Testing and counseling topics were assigned to visits based on gestational age. Interdisciplinary weekly Pod meetings provided coordination of care. A retrospective chart review was performed. The primary endpoints were the number of prenatal care visits and number of providers seen. Results . After PodCare implementation, more patients choose care with the low-risk physician team (42% compared to 26%). Study subjects included 85 women in 2013 and 165 women in 2014. The median number of visits decreased from 13 to 10 (p < 0.00004) and the median number of providers seen decreased from 7 to 5 (p < 0.0000008). Conclusion . PodCare increased the value of individual prenatal care by decreasing the number of visits, increasing continuity, and providing care coordination. The model provides a robust experience in interdisciplinary care. The PodCare model may be successful at other academic institutions.